Early Childhood Education Curriculum Application KurPA In Improving Early Childhood Education Learning Management in Cluster 2, Garut City District, Garut Regency - Tazkiah, Nita; Puridawaty, Brigita (Kirana Publisher (KNPub), 2025)
This study aims to develop and evaluate the effectiveness of the KurPa (Early Childhood Education Curriculum) application in improving Early Childhood Education learning management in Cluster 2, Garut City District. The development method used is the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). While data processing is carried out using a qualitative and quantitative mixed method approach. Qualitative data processing is carried out for feasibility testing through expert testing and collecting interview notes, and documentation. Quantitative data processing for effectiveness testing through a one-way t-test with a significance of 0.05 in a large group of preexperimental one group pretest posttest. The results of the study obtained a sig. (2-tailed) value of 0.000 indicating that 0.000 <0.05 which proves that the H1 hypothesis is accepted, namely that there is an increase in learning management with the KurPa Application. Thus, the KurPa application significantly increases teacher efficiency in preparing learning plans, increases parental involvement in the learning process, and provides more effective feedback for teachers and parents. In addition, the KurPa application is also considered user-friendly and easy to use by Early Childhood Education teachers. This study concludes that the KurPa application can be an effective solution in improving Early Childhood Education learning management.